CTIM-08. SAFETY, EFFICACY, AND SURVIVAL RESULTS FROM A PHASE 1 STUDY OF THE ONCOLYTIC ADENOVIRUS DNX-2401 FOLLOWED BY STANDARD OF CARE RADIOTHERAPY FOR NEWLY DIAGNOSED DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (12th November 2021) - Pérez-Larraya, Jaime Gállego; Garcia-Moure, Marc; Patiño-García, Ana; González-Huarriz, Marisol; Van der Lugt, Jasper; Astigarraga, Itziar; García-Ariza, Miguel; López-Ibor, Blanca; Jones, Chris; Mackay, Alan; Diez-Valle, Ricardo; Fueyo, Juan; et al.
Abstract: BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is the most lethal pediatric brain tumor. Median overall survival (OS) with standard of care radiation therapy (RT) is approximately 8-10 months and 2-year survival is < 10%. A Phase 1 single-center study was conducted to evaluate the oncolytic adenovirus, DNX-2401 (tasadenoturev), followed by RT for DIPG. METHODS: Newly-diagnosed DIPG patients 1-18 years old received a tumor biopsy through the cerebellar peduncle followed by intratumoral injection of 1e10 – 5e10 vp DNX-2401 and conventional RT 1-3 weeks later. RESULTS: Subjects were enrolled (n=12) from December 2017 to January 2020 and had a median age of 9 years (range 3-18) and Lansky/Karnofsky performance scores of 90-100 (n=4; 33%) or 70-80 (n=8; 67%). Genetic assessment was completed for 11 subjects (92%) and histone 3 K27M mutations were identified in 10 subjects, including H3F3A (n=8), HIST2H3C (n=1), and HIST1H3B (n=1); 1 subject was H3 wildtype (n=1). TP53 mutations were identified in 5 subjects (42%). DNX-2401 was administered followed by RT (n=11; 92%). No dose-limiting toxicities were observed and the treatment regimen was well-tolerated. The most commonly reported adverse events (≥ 5 subjects), regardless of study drug relationship, include asthenia, headache, vomiting, pyrexia, and neurological deterioration. Three serious adverse events were reported including grade 3 abdominal pain, grade 3 lymphopenia, and grade 3 clinical deterioration. Tumor reductions were reported for 9 subjects (75%), including 2 confirmed (17%) and 2 unconfirmed (17%) responses per RAPNO criteria. As of the data cutoff, median OS is 19.7 months and OS-24 is 32% with follow-up ongoing for 3 subjects (26.9, 25.6, 13.7 months). CONCLUSIONS: DNX-2401 followed by RT can be safely administered to DIPG. Survival outcomes are encouraging, thus warranting further evaluation in a Phase 2 study.